ENHANCED DIVERSIFICATION OF TOURISM SERVICES THROUGH DIGITAL TRANSFORMATION IN REGIONAL TOURISM SECTORS - Raxmanova , Dildora Toshmurzayevna; Yuldosheva , Zulfizar Sayfullayevna (Educational Research in Universal Sciences, 2023)
As the world becomes increasingly digitized, traditional industries have to adapt and change in order to remain relevant and competitive. The tourism industry, which is largely dependent on travelers, is one such industry that must evolve to keep up with the advancements in technology. The concept of diversification of tourist services has become important as the industry has expanded and new markets have become available. In this dissertation, we will examine the mechanisms currently in place for diversification of tourist services in various regions and the ways in which they can be improved using digital technologies. The concept of diversification of tourist services refers to the expansion of the range of services and products available to tourists in a particular location. It involves offering a variety of experiences that appeal to a broad range of visitors such as cultural, recreational, and adventure activities. The purpose of diversification of tourist services is to broaden the tourism offerings of a particular place to cater to a wider range of tourists. This can increase the number of visitors to that area and provide additional revenue streams. The greater the variety of tourist services available, the more attractive the destination becomes to a diverse range of tourists. As such, diversification of tourist services is essential in promoting the growth and sustainability of the tourism industry.